2018
DOI: 10.21608/adjalexu.2018.57637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biaxial Flexural Strength and Translucency of Multichromatic Translucent Zirconia and Lithium Disilicate Ceramics

Abstract: INTRODUCTION: Full-contour (monolithic) zirconia restorations are gaining in popularity. High translucent zirconia materials and multilayered zirconia blocks might help to overcome the aesthetic drawbacks of traditional zirconia for fabrication of monolithic restorations OBJECTIVES: Were to evaluate the biaxial flexural strength and translucency of CAD/CAM: multichromatic ultra-translucent zirconia and comparing it with multichromatic high translucency Lithium Disilicate glass-ceramic. MATERIALS AND METHODS40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Our results were in accordance with a study performed by Eduardo M. Murioz et al (2017) (36) where AMZ (anterior cubic monolithic zirconia) had lower biaxial flexural strength values in comparison with PMZ (posterior non-cubic monolithic zirconia) which was affected by mechanical and hydrothermal aging. Our results were also similar to Jihad G. Hamed et al (37) who stated that Katana UTML group had significantly higher biaxial flexural strength values than those in IPS e.max Press Multi group.…”
Section: Discussionsupporting
confidence: 91%
“…Our results were in accordance with a study performed by Eduardo M. Murioz et al (2017) (36) where AMZ (anterior cubic monolithic zirconia) had lower biaxial flexural strength values in comparison with PMZ (posterior non-cubic monolithic zirconia) which was affected by mechanical and hydrothermal aging. Our results were also similar to Jihad G. Hamed et al (37) who stated that Katana UTML group had significantly higher biaxial flexural strength values than those in IPS e.max Press Multi group.…”
Section: Discussionsupporting
confidence: 91%
“…In order to fulfill the aesthetic requirements, several generations of zirconia ceramics were introduced. Many researchers have already investigated the microstructure and the basic intrinsic properties of these highly translucent Y-PSZ (Hamed et al, 2018;Mao et al, 2018;Kolakarnprasert et al, 2019;Sen and Isler, 2019). The phase composition and mechanical properties (mainly strength and toughness) of new-generation highly translucent zirconia are different from those of conventional zirconia (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It was clearly shown in the results presented in Table 4 that Zirconia has a better flexural strength in all the groups followed by E-max and then Gradia. Jihad et al (34) similarly found that Zirconia materials showed superior biaxial flexural strength values than the lithium disilicate glass ceramics. According to Piconi and Maccauro ( 35) Zirconia is strongly dependent on its grain size, thus, it cannot be easily transformed.…”
Section: Discussionmentioning
confidence: 98%